2015
DOI: 10.1002/jrs.4708
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectra of water in fluid inclusions: I. Effect of host mineral birefringence on salinity measurement

Abstract: International audienceRaman microspectrometry of water in individual aqueous fluid inclusions can provide chemical information about fluid composition, in particular the concentration of chloride ions. The regular method consists in correlating the deformation of the OH stretching vibration band of liquid water in the region assigned to hydrogen-bonded OH groups with chloride concentration. In the present study, a set of seven different minerals with various birefringence properties (barite, calcite, celestine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 25 publications
2
22
0
2
Order By: Relevance
“…Natural water-rich CO 2 fluid inclusions hosted in Kyanite (Zambia) (H 2 O-CO 2 -NaCl, with T m (car) = -56.6 °C) (Caumon et al, 2015), H 2 O-NaCl and H 2 O-NaOH synthetic fluid inclusions, with respectively T e = -21.2 ° and T m (ice) = -0.4 °C were used to calibrate the analytical device. The following phase transitions were measured when it was possible:…”
Section: Microthermometrymentioning
confidence: 99%
“…Natural water-rich CO 2 fluid inclusions hosted in Kyanite (Zambia) (H 2 O-CO 2 -NaCl, with T m (car) = -56.6 °C) (Caumon et al, 2015), H 2 O-NaCl and H 2 O-NaOH synthetic fluid inclusions, with respectively T e = -21.2 ° and T m (ice) = -0.4 °C were used to calibrate the analytical device. The following phase transitions were measured when it was possible:…”
Section: Microthermometrymentioning
confidence: 99%
“…Salinity is expressed as weight equivalent percent NaCl (wt.% NaCl eq.) and has been calculated using the measured ice melting temperature (Tm Ice) with the equation of Bodnar (1993) and Raman analyses (Caumon et al, 2013(Caumon et al, , 2015.…”
Section: Fluid Inclusion Analysesmentioning
confidence: 99%
“…Caumon and co‐workers determined the Raman spectra of water in fluid inclusions to study the effect of host mineral birefringence on salinity measurement. They find that a good knowledge of the polarization properties of the optical devices of the Raman spectrometer and a correct positioning of the sample thus result in salinity (chloride concentration) measurements with the same accuracy as classic microthermometry . Diez‐y‐Riega et al .…”
Section: Liquids Solutions and Liquid Interactionsmentioning
confidence: 99%
“…They find that a good knowledge of the polarization properties of the optical devices of the Raman spectrometer and a correct positioning of the sample thus result in salinity (chloride concentration) measurements with the same accuracy as classic microthermometry. [140] Diez-y-Riega et al reported thermal lens detection of one and two-color laser excitation of benzene in cryogenic liquid solutions. They used a three-level model to explain signal enhancement with respect to one-color laser excitation under the same experimental conditions.…”
Section: Liquids Solutions and Liquid Interactionsmentioning
confidence: 99%